Improving Eleventh Grade’s Speaking Skill Through Youtube Video at Man 5 Jombang - Dinda Arofatus Sa’adah; Sakhi Herwiana; Mukminatus Zuhriyah (E-Link Journal, 2024)
English is a foreign language in Indonesia and has an important role in education. There are four skills in learning English, namely listening, speaking, reading and writing. These skills are important to master without neglecting each other. For most people, mastery of speaking skills is the most important aspect in learning a foreign language and the success of mastering a language is measured by the ability to have a conversation. There are many ways to learn speaking skills, one of which is through media, namely YouTube. This study aims to determine whether the use of YouTube Videos can improve the speaking skills of students in grade eleven at MAN 5 Jombang in the 2020/2021 academic year. This study uses the collaborative classroom action research (CCAR) method. The results of the study showed that the use of YouTube Videos can improve students' speaking skills, as evidenced by the results of the post-test with a success rate of 94% and the questionnaire, where 74% of students were enthusiastic about this media.